Inovasi Olahan Produk Pertanian Stik Singkong Keju dan Penguatan Digital Marketing di Desa Jambudesa - Arbika, Cadar Isya; Majid, Habib Ilham; Mar’ah, Dyah Awaliyah; Faa'idah, Riska Nabil; Listiawati, Aliza; Chairil, Ludfi; Prayoga, Ipuk Adi (STIE Pelita Nusantara, 2025)
The Community Service Program (KKN) is a program that involves students as an inseparable part of the tri dharma of higher education, focusing on honing students’ abilities to apply all forms of knowledge acquired during lectures. Jambudesa Village, Purbalingga Regency is one of the locations for KKN implementation. Based on observations in this village, most of the local community are farmers. One of them is the cassava farmers who rely on it for their livelihood. At the time of the cassava harvest, farmers sell it directly to collectors at a price of around one thousand rupiah per kilo, as mentioned by one of the farmers. Therefore, an innovation program for food products based on local agricultural products, including cassava, was implemented. There are several reasons why this program was initiated, mainly to increase the market value of cassava. To foster creativity for the local community, especially for housewives, and to utilize the abundant agricultural products in the surrounding environment. In addition to product innovation, students also present a digital marketing socialization work program aimed at the sustainability of the product innovation creation, which is expected to expand the market, improve competitiveness, and maximize the economic potential of the community in the technological era. The results of the activities show an increase in community skills in processing cassava, the creation of unique food products, and the initial ability of the community to utilize social media to market products.